ANALISIS PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA NON FISIK, DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION (Studi pada PT Indotirta Jaya Abadi, Ungaran) - Fujiana, Rima; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2016)
High employee turnover rates have negative impacts for the company, such as the loss of the training costs which have been invested for employees, new employees recruitment expenses, and delay the company's plans due to the search of new employees. It can get worse if the company loses employees who are experienced and have a good performance.Therefore, this study aimed to determine the effect of job satisfaction, non-physical work environment, and organizational commitment to employee turnover intention. Research was conducted on the production employees of PT Indotirta Jaya Abadi, Ungaran. Data collection methods used in this study was a questionnaire. The number of samples are 60 respondent. Data were analyzed using multiple linear regression analysis with SPSS.The result showed that job satisfaction and organizational commitment have negative significant affect toward turnover intention, while the non-physical work environment does not significantly affect toward turnover intention. Furthermore, the coefficient of determination in this study is 0,217 which means that the independent variable in this study may explain the dependent variable at 21,7 percent, while 78,3 percent is explained by other factors outside the model.